2002
DOI: 10.1161/hh0302.104466
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the β-Catenin/T-Cell Factor Signaling Cascade in Vascular Remodeling

Abstract: Abstract-␤-Catenin and T cell factor (Tcf) are distal components of the highly conserved Wnt pathway that govern cell fate and proliferation in lower organisms. Thus, we hypothesized that the regulation of ␤-catenin and Tcf played a critical role in vascular remodeling. The first objective was to define ␤-catenin expression in vascular smooth muscle cells (VSMCs) after balloon injury. Indeed, ␤-catenin mRNA and protein were significantly elevated 7 days after balloon injury in the rat carotid artery. We hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
193
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(201 citation statements)
references
References 40 publications
6
193
1
1
Order By: Relevance
“…Altogether, this data suggest Wnt3a alters the phenotype of vascular smooth muscle cells. As Wnt signaling is upregulated after vascular injury, 7,14 this data highlight a potential role for Wnt3a in controlling smooth muscle cell phenotype during vascular wound repair and remodeling processes.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Altogether, this data suggest Wnt3a alters the phenotype of vascular smooth muscle cells. As Wnt signaling is upregulated after vascular injury, 7,14 this data highlight a potential role for Wnt3a in controlling smooth muscle cell phenotype during vascular wound repair and remodeling processes.…”
Section: Discussionmentioning
confidence: 83%
“…These channels are comprised of subunit proteins encoded by the multigene connexin family, of which connexin 43 is the predominant connexin expressed by vascular smooth muscle cells. 28 It has previously been reported that connexin 43 expression is upregulated in smooth muscle cells in response to injury in rodent models and in early human atherosclerosis, situations in which elevated Wnt signaling has been reported 7,14 and in which increased extracellular matrix synthesis is well documented. 3,38 Reducing connexin 43 expression has been shown to inhibit lesion development in rodent models of atherosclerosis and acute vascular injury, [39][40][41] suggesting potential pro-atherogenic functions for gap junction communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Wnt signaling in ECs has been shown to activate proinflammatory gene expression via inhibition of canonical Wnt signaling and activation of the noncanonical Ca 2+ ‐dependent pathway via ligand Wnt5a 88, 89. Several studies have demonstrated a direct link between canonical Wnt signaling via ligands Wnt1, Wnt2, and Wnt3a and arterial smooth muscle cell proliferation, which underlies the intimal thickening stage of atherosclerosis 20, 21, 90, 91. Canonical Wnt signaling and LRP5 have also been directly implicated in the promotion of foam cell formation 6.…”
Section: Implication Of Wnt Signaling In Atherosclerosis Pathologicalmentioning
confidence: 99%
“…Interestingly, a specific role for TCF-4 has been shown in the process of vascular remodelling. Moreover, transcriptional activation of TCF-4 turns on the nuclear factor-.B signalling pathway, which regulates inflammatory signalling pathways [5]. Data from the MONICA/KORA Surveys showed that the T allelemodel assessment of per cent beta cell function and fasting insulin, suggesting a role in pancreatic beta cell function [3].…”
Section: Introductionmentioning
confidence: 99%